Child Care and the Development of Behavior Problems among Economically Disadvantaged Children in Middle Childhood - Votruba-Drzal, Elizabeth (2010)
Research examining the longer term influences of child care on children’s development has expanded in recent years, but few studies have considered low-income children’s experiences in community care arrangements. Using data from the Three-City Study (N = 349), this study examines the influences of child care quality, extent and type on low-income children’s development of behavior problems during middle childhood (7–11 years old). Higher levels of child care quality were linked to moderate reductions in externalizing behavior problems. High quality child care was especially protective against the development of behavior problems for boys and African American children. Child care type and the extent of care that children experienced were generally unrelated to behavior problems in middle childhood.